Sinonasal sarcomas management: an international consensus statement - Vinciguerra, Alessandro; Caspani, Francesca; Valentini, Marco; Camarda, Anna Maria; Provenzano, Salvatore; Wang, Eric W.; Meço, Cem; Ferrari, Marco; Surda, Pavol; Harrabi, Semi; Campos, Fernando Augusto Batista; Broto, Javier Martin; et al. (International forum of allergy & rhinology, 2025)
Introduction Sinonasal sarcomas are exceedingly rare entities, constituting less than 7% of head and neck sarcomas. Their complex histology needs specialized treatment, which is often based on multimodal approaches including surgery, radiation therapy, and/or chemotherapy. This manuscript aims to gather expert opinions to establish common management principles for sinonasal sarcomas. Methods This international consensus followed a modified Delphi method in seven steps, including statements definition by the core group, expert panel recruitment, and a two-round survey. Sixty-two statements on sinonasal sarcoma management were developed. Experts from multiple continents participated, and results were anonymized and analyzed between March and May 2025. Results A total of 44 invited experts were recruited, 43.2% otorhinolaryngologists/head and neck surgeons, 31.8% medical oncologists, and 25% radiation oncologists. Participants varied in age and experience, representing Europe (70.5%), North America (18.2%), South America (6.8%), and Asia (4.5%). Among all histologies, biphenotypic sarcoma, chondrosarcoma, leiomyosarcoma, and myofibrosarcoma are principally treated with an upfront surgical management, differently from Ewing sarcoma and rhabdomyosarcoma in which chemotherapy, eventually associated with radiotherapy, is often chosen. In the remaining histologies (angiosarcoma, liposarcoma, malignant peripheral nerve sheath tumor [MPNST], osteosarcoma, and synovial sarcoma), a precise multimodal treatment is less standardized and needs to be discussed on a case-by-case basis. Conclusion Sinonasal sarcomas require a histology-driven approach to determine upfront treatment, whether surgical, medical, or multimodal. Despite this structured strategy, prognosis remains highly variable across subtypes. Multidisciplinary evaluation and individualized management in referral centers are crucial to address the biological diversity and anatomical complexity of these rare malignancies.